Resin tapping activity as a contribution to the management of maritime pine forest - Palma, Amélia (2017)
Aim of the study: In this work potential resin yield in a region of high forest ability where maritime pine is the main species was estimated in order to understand the viability of promoting resin exploitation. Area of study: This study was conducted in Castro Daire County in central region of Portugal. Material and methods: To quantify the resin yield of trees tapped for the first time two plots were installed in a maritime pine stand with average tree age 65 years. Before the beginning of the resin tapping, dendrometric tree variables were measured. Also, in a neighbouring stand, 25 trees were selected to check the relation between tree dbh and resin yield. Gum resin from every tree was weighted during the season. Estimates of potential resin yield in Castro Daire County were made based on data from National Forest Inventory plots, resin tapping legislation and resin yield values obtained in the field. Two scenarios were considered: high and low resin yield. To understand the intentions of forest owners towards restarting resin tapping activity 16 maritime pine forest owners were interviewed. Main results: The results point out a high yield potential capacity for gum resin production in the County: values between 2,025 and 5,873 tons were obtained. Research highlights: Results may highlight the important socio-economical role of the resin tapping activity and can be used to support national forest policies to the resin sector and give forest owners motivation to reactivate resin tapping activity